Extracorporeal photopheresis in the treatment of acute graft-versus-host disease: A multicenter experience. (October 2021) - Batgi, Hikmettullah; Dal, Mehmet Sinan; Erkurt, Mehmet Ali; Kuku, Irfan; Kurtoglu, Erdal; Hindilerden, Ipek Yonal; Kaya, Emin; Berber, Ilhami; Ulas, Turgay; Altuntas, Fevzi
Abstract: Background and objectives: Extracorporeal photopheresis (ECP) is one of the second-line treatment strategies in steroid-refractory acute graft-versus-host disease (aGvHD). We aimed to share our multicenter experience using ECP in our steroid-refractory aGvHD patients. Materials and methods: A retrospective observational series of 75 aGvHD patients from 4 transplant centers were analyzed. All ECP procedures were performed with the off-line system. All patients received ECP as second-line therapy. Results: 74.7 % of aGvHD patients were grade 3 or 4. The overall response rate was 42.7 % (32/75) in aGvHD including 17 complete responses (22.7 %). Median follow-up was 6 months (range, 1–68). Median overall survival (OS) was 5 months for non-responders and 68 months for responders (p < 0.001). Twenty-seven (36 %) patients are alive, and 48 (64 %) patients have died. Conclusions: Early initiated ECP could be an effective treatment alternative in patients with steroid-refractory aGvHD.